HIV Co-infected Patients with HBV And HCV- A Review - A, Aliakhtar; HK, Amer; A, Tanveer; M, Salman (Indian Journal of Pharmacy Practice)
The prevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV) co-infection with HIV is significant. Co-infection with the two viruses is not uncommon. It is well established that worldwide approximately 4 to 5 million persons are co-infected with HIV. There is a considerable variation in the prevalence of co-infection in different areas. In the treatment of HIV infection, the use of highly active antiretroviral therapy (HAART) is measured and its discovery has been one of the most useful and dramatic advances in the field of medicine. Highly active antiretroviral therapy was introduced in Malaysia in 1997 for treating HIV infection. The purpose of this study is to investigate the prevalence of HBV and HCV co-infection with HIV. The initiation of HAART for human immune deficiency virus has led an era to focus on other leading causes of morbidity such as hepatitis B and hepatitis C. We will review the evaluating effects of highly active antiretroviral therapy on HIV positive patients co-infected with HBV and HCV and find out its possible outcomes. Knowledge of the effects of various treatments as well as interaction between these viruses is the key to understanding and effectively treating these patients. Recent reviews have discussed many aspects of treatment. We summarize the advanced studies regarding to the progression of HAART including effects of co-infection with hepatitis B and C virus as well as its pharmacotherapeutic outcomes.